Structural and durability analysis of a novel re-roofing concept. Issue 4 (2nd October 2017) - Richman, Russell; Bentz, Evan; Jermyn, Denver; Sun, Chang
Abstract: Metal roof decks in long-span light steel structures can become damaged and obsolete by corrosion should the roofing system become compromised. Re-roofing is conducted by either removing and replacing damaged areas (resulting in suspension of interior operations and lost revenue) or installing new decking directly over the damaged areas which can transfer corrosion to the new deck. This research conducts structural and durability analyses on a novel proposed re-roofing concept that installs a new metal roof deck over the existing deck by using a proprietary deck strap resulting in no interruption of interior processes. Preliminary structural analysis shows the proposed concept to be applicable to generic conditions around Southern Ontario. Recommendations for project specific structural analysis are made. Durability analysis demonstrates that the proposed concept system improves hygrothermal performance of the roof assembly in all cases except when insulation in the existing roof assembly is saturated. Saturated insulation should be removed prior to installing the re-roofing system.